INFORMATIONAL PORTAL «PLANT BIOTECHNOLOGY» – INTERNET RESOURCE TO SUPPORT EXPERIMENTS IN PLANT GENE ENGINEERING, GENETICS AND WHEAT BREEDING - A. V. Kochetov; O. G. Smirnova; S. M. Ibragimova; D. A. Rasskazov; D. A. Afonnikov; M. A. Genaev; A. V. Doroshkov; T. A. Pshenichnikova; A. V. Simonov; E. V. Morozova (Вавиловский журнал генетики и селекции, 2014)
New Internet-resource to support the research in plant biotechnology is presented. This Internet portal contains specialized modules (databases and software) and allows users to combine these modules to solve various tasks as well as it permits the further resource development by addition of new modules. Currently the resource contains the database of external informational sources, the database on promoters for plant transgenesis, the database on translational enhancers for plant transgenesis, and the database WheatPGE to support the experiments in a wheat breeding. The resource is available at ICG www-site (http://bioagrotech.bionet.nsc.ru/).